Association of body mass index, sleep quantity, sleep quality and sleepiness among express bus driver. (1st March 2011) - Mani, K; Fazelin, N; Ismail, S
Abstract : The number of road crashes involving trade vehicle especially buses and lorries are increasing every year. The number of commercial vehicles, which involved in crashes increased by 25.35% within 5 years from 2000 to 2005. Besides that, percentage of road crashes involving buses also had increased alarmingly by 131.25%. Driver sleepiness is a potentially important risk factor of road crashes and related injuries. The main objective of this study is to identify the association between body mass indexes, sleep quantity and sleep quality towards sleepiness among express bus drivers. This is a cross-sectional study conducted in Johor Bahru, Johor. Weighing scale and body metre were used in measuring weight and height while standardise questionnaire which consist of three parts namely part 1 covering socio demographic details, part 2 contains Epworth Sleepiness Scale and part 3 contained 7 days self reported sleep log. Sleepiness level was measured using Epworth Sleepiness Scale. Measurement was conducted before the respondents start their job. Eighty-five respondents were involved and 18 (21.2%) of them were found to be sleepy. χ 2 test or Fishers exact test revealed that there were only three variables found to be significant. They are body mass index (p=0.002), sleep quantity (p=0.038) and working experience (p=0.006) whereas four variables found to be insignificant and they are age (p=0.050), sleep quality (p=0.617), driving duration (p=0.078) and driving distance (p=0.063). From the result, the factors that influenced the sleepiness level among the express bus drivers were body mass index, sleep quantity and working experience.